(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
The article reveals the nature of internal and external factors associated with human economic culture, classifies their rational use, and also discusses issues of preventing economic costs and reducing their impact on the green economy while complying with the requirements of the green economy